Strategic Vagueness and Appropriate Contexts - Kris De Jaegher; R. van Rooij (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
This paper brings together several approaches to vagueness, and ends by suggesting a new approach. The common thread in these approaches is the crucial role played by context. Using a single example where there is a conflict of interest between speaker and listener, we start by treating game-theoretic rationales for vagueness, and for the related concepts of generality and ambiguity. We argue that the most plausible application of these models to vagueness in natural language is one where the listener only imperfectly observes the context in which the speaker makes her utterances. We next look at a rationale for vagueness when there is no conflict between speaker and listener, and which is an application of Horn's rule. Further, we tackle the Sorites paradox. This paradox apparently violates standard axioms of rational behaviour. Yet, once it is taken into account that vague language is used in an appropriate context, these axioms are no longer violated. We end with a behavioural approach to vagueness, where context directly enters agents' preferences. In an application of prospect theory, agents think in terms of gains and losses with respect to a reference point. Vague predicates now allow agents to express their subjective valuations, without necessarily specifying the context.
Keywords: 330; Vagueness; signalling games; decision theory; prospect theory